Therapy of Pseudomonas aeruginosa Infections with Tobramycin - Blair, Donald C. (1975)
The efficacy of tobramycin in doses of 2.7 to 5.6 mg/kg per day in 29 courses of therapy in 25 hospitalized patients with serious Pseudomonas aeruginosa infections was studied. Eighty-three percent of the P. aeruginosa strains showed zones of inhibition of 16 mm or more around a 10-μg tobramycin disk in the Bauer-Kirby disk method. Tobramycin minimal inhibitory concentration ranged from <0.05 to 1.5 μg/ml (microtiter twofold dilution method); for gentamicin they ranged from 0.05 to 6.2 μg/ml; corresponding geometric means were 0.19 and 0.49 μg/ml. Therapy was given for a median of 10 days (mean 19, range 1 to 83). The clinically satisfactory response rate for the 29 courses of therapy was 52%: critically ill, 44%; seriously ill, 50%; moderately ill, 80%. The response rates for various sites of infection were bone and cartilage, 100%; urinary tract infection, 56%; wound, 50%; respiratory tract, 67%; septicemia, 40%; abscess, 0%; burns, 44%. No adverse reactions were seen. Serum concentration (μg/ml ± standard deviation) of tobramycin determined by an agar-well plate method, were 4.81 ± 2.17 (1 h); 3.24 ± 1.43 (2 h); 2.35 ± 1.30 (4 h); and 1.40 ± 1.09 (8 h). Tobramycin appears to be as effacacious as gentamicin in the treatment of serious P. aeruginosa infections and has a theoretical advantage of lower minimal inhibitory concentration for P. aeruginosa. The data suggest that, for life-threatening infections, dosages of tobramycin may need to be increased over those used in this study.